2012
DOI: 10.2134/agronj2011.0323
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Interrelationships between Wheat Phenology, Thermal Time, and Terrain Attributes

Abstract: Spatial variation of winter wheat (Triticum aestivum L.) phenology across complex terrain has received little attention despite its importance for assessing overall crop status and making key precision management decisions. Temperature is the environmental factor explaining the greatest variation in phenology, and temperature varies across a landscape. Our primary hypothesis was that variability in thermal time (TT) by landscape position could explain the phenological variation, with a secondary hypothesis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Meteorological SOS represents an average temperature status for a period of time and coincides with the cumulative effect of temperature to the onset of vegetation spring phenology [ Ault et al ., ]. We chose SOS as the study phenological event because (1) it determines the length of the growing season and is crucial for grain yield [ Wang et al ., ; Salazar‐Gutierrez et al ., ], (2) the algorithm for satellite‐based SOS identification is well established, and (3) the shift in winter wheat SOS is exclusively driven by temperature rather than differences in the cultivars and cropland management [ McMaster et al ., ; Xiao et al ., ], and thus, the observed changes in winter wheat SOS should synchronize with meteorological SOS dynamics. Our results demonstrated that compared with ground observations, satellite data correlated more closely with meteorological data in terms of both long‐term trends and interannual variations of winter wheat SOS.…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological SOS represents an average temperature status for a period of time and coincides with the cumulative effect of temperature to the onset of vegetation spring phenology [ Ault et al ., ]. We chose SOS as the study phenological event because (1) it determines the length of the growing season and is crucial for grain yield [ Wang et al ., ; Salazar‐Gutierrez et al ., ], (2) the algorithm for satellite‐based SOS identification is well established, and (3) the shift in winter wheat SOS is exclusively driven by temperature rather than differences in the cultivars and cropland management [ McMaster et al ., ; Xiao et al ., ], and thus, the observed changes in winter wheat SOS should synchronize with meteorological SOS dynamics. Our results demonstrated that compared with ground observations, satellite data correlated more closely with meteorological data in terms of both long‐term trends and interannual variations of winter wheat SOS.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor was placed at a 1‐m height above the soil surface and maintained at this height regardless of the canopy height, which for our variety and environments was always less than the sensor height. Further details for this experiment can be found in McMaster et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Weather data are given for different intervals related to seasons or periods for developmental stages. Updated fromMcMaster et al (2012).…”
mentioning
confidence: 99%
“…The field site has been described and studied previously regarding terrain analysis [31], spatial scaling of infiltration rates [32], temporal dynamics of measured soil moisture at different landscape positions [33], one-dimensional simulations of soil moisture ( [14,34]), and interrelationships between terrain and wheat development [35]. The watershed defined by an outlet at the eastern edge of the cropped field has an elevation range of 1559-1588 m, a mean annual precipitation of approximately 350 mm, and a mean annual evapotranspiration of approximately 1200 mm.…”
Section: Case Study Of a Geotop Application In Omsmentioning
confidence: 99%